Seroprevalence of brucellosis in cows and buffaloes - Tehmina Aslam; Sikandar Hayat; Sobia Alyas; Azhar Ilyas (International Journal of Applied and Experimental Biology)
Brucellosis poses a significant zoonotic risk to humans and animals, and is caused by the Gram-negative bacteria of the Brucella species. In cows and buffaloes, infection is typically attributed to Brucella abortus, often resulting in abortion during late pregnancy and posing a subsequent risk of sterility in females. The current study aimed to assess the seroprevalence of brucellosis in cows and buffaloes in district Kasur, Pakistan. A total of 400 blood samples were randomly collected from cows and buffaloes in the district. The Rose Bengal Plate Test (RBPT) was initially employed for screening the blood serum samples of each animal, with Indirect ELISA serving as a confirmatory test. Higher seroprevalence rates were observed in females compared to those in males in both tests. Sex-wise, higher incidence of brucellosis in cows was observed, with a prevalence of (7%)/(5%) in females compared to that (2%)/(1%) in males, as detected by the RBPT and iELISA tests, respectively. Similarly, buffaloes exhibited a higher prevalence of brucellosis in females, with rates (10%)/ (8%) compared to (3%)/(1%) in males, via RBPT and iELISA, respectively. A total of 200 cow and 200 buffalo samples were analyzed, that revealed a seroprevalence of (4.5%)/(3%) in cows and (6.5%)/(4.5%) in buffaloes, respectively, using RBPT and iELISA. Overall, out of a total of 400 serum samples, 22 from cows and buffaloes were tested positive through RBPT, while 15 samples from both species were seropositive via iELISA. The overall seroprevalence of brucellosis in the district was found to be 5.5%/3.75% through RBPT and iELISA, respectively. This study highlights a significant challenge for the livestock being rared in district Kasur.